Multimedia Development Based on The Assemblr EDU Application in Human Reproductive System Material for Grade XI High School Students - Devita Sulistiana; Marinda Sari Sofiyana; Elsha Dewi Anggraini (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2026)
Based on an analysis of potential and problems involving 90 students in class XII in 3 top high schools in Blitar city/regency in 2023, the specific learning styles were 31,1% kinesthetic, 7,8% auditory, and 58,9% audiovisual. Data states that 64.4% of students find the material on the human reproductive system difficult to understand. Based on interviews with 3 biology teachers, it was revealed that preparing differentiated learning media is time-consuming. Teachers still predominantly use PPT-based media. The design of the multimedia, based on the Assemblr EDU application, is informed by data indicating that 93.3% of students favor multimedia-based learning. The objective of this Research and Development (R&D) is to develop and assess the feasibility of a multimedia platform based on the Assemblr EDU application as a teaching medium for material on the human reproductive system for grade XI high school students. This study research utilizes the R&D method, the research design following Sugiyono’s development model, limited to 7 stages with a quantitative descriptive approach. The feasibility test, validated by material, language, and media experts, yielded scores of 92.5%, 90.6%, and 89.23%, respectively, all falling within the “Very Feasible” criteria. Additionally, the feasibility test, conducted through limited trials with teachers and students, yielded scores of 87.3% and 93.2% under the “Very Feasible” criterion. Thus, the developed Assemblr EDU application-based multimedia material on the human reproductive system for grade XI High School Students is considered suitable for learning activities